SFCW software-defined radar using LabVIEW and USRP for subsurface sensing - Ardzemi, Nor Hazima; Mohd. Isa, Farah Nadia; Abdul Malek, Norun Farihah; Mohamad, Sarah Yasmin; Nordin, Rosdiadee (IEEE, 2022)
In this paper, we describe the experiment of a dual-channel stepped-frequency continuous wave (SFCW) radar system using LabVIEW and NI USRP N210. The step-by-step of the radar design is discussed, including the SFCW signal generation, the USRP-LabVIEW connection, and the transmit/receive process of the system.